George Elliott Clarke’s George and Rue: a multicultural view - Abbas, Hussein Ali; Mani, Manimangai (Center for Resource, Research and Publication Services, 2018)
In her theory of Critical Multiculturalism (2004), the Canadian theorist Sneja Gunew suggests that things produce meanings only when they are placed within contexts. Once these things are put out of context, the meanings are lost. In 1949, for instance, two Black brothers, George and Ruthus Hamilton, killed a White taxi driver for money. The two brothers were arrested several days later and were sentenced to death. Officially, the incident was reported as a crime, and punishment is necessary for the safety of the whole society. Once it is contextualized within the story of African Canadians by a fiction entitled George and Rue (2005), the incident produces a different meaning. It criminalizes the White Canadian society that has oppressed all Blacks by giving them no jobs to survive. This paper examines George Elliott Clarke’s George and Rue by using the critical idea of contextualization, one of the main ideas upon which the theory of Critical Multiculturalism is established. Critical Multiculturalism is a Postcolonial theory which is devoted to examine the experiences of immigrants in Western countries. It looks at the presence of non-Europeans in these Western countries as a new stage of colonialism. Thus, the relationship between the White majority and non-White minorities in Canada becomes a relationship between the colonizers and the colonized. By the merit of contextualization, the stories that have officially been narrated about the immigrants, appear with different meaning in fictions written by non-White authors. Thus, contextualization has contributed to create a gap between the official and literary narratives over the stories of non-White Canadians, called immigrants.